TANGGUNG JAWAB PELAKU USAHA TERHADAP KERUGIAN KONSUMEN - Bustomi, Abuyazid (Solusi, 2018)
In Article 1 of Act Number 8 of 1999 concerning consumer protection, it is stated that consumers are every person who uses goods and or services available in the community, both for the benefit of themselves, their families, other people, and other living things and not for trading. Consumer protection is a matter of legal protection given to consumers in an effort to obtain goods and services from possible losses due to their use, then the law of consumer protection can be said as a law governing the provision of consumer protection how guarantees are protected consumer rights and how to enforce regulations through state administration law, criminal law, and civil law so that the fulfillment of consumer rights is fulfilled, the goods and services of the business conduct products will be protected as such. The responsibility of the business actor for the loss of the consumer is to provide compensation for the damage, pollution, and or loss of the consumer due to consuming goods and or services produced or traded. Payment of compensation is the main responsibility of the business actor, compensation in accordance with Law No. 8 of 1999 concerning Consumer Protection can be in the form of: refunds, replacement of similar goods and or services of equal value, health care, and compensation.